The Effect of Capital Turnover on Profits in PT. Pro Car INTL Finance Palopo Branch - S. Sahabuddin; S. Sudirman (Manunggal Halim Jaya, 2026)
The purpose of the research is to find out the capital turnover that has a significant effect on the profit at PT. Pro Car INTL Finance Palopo Branch. Cash turnover and receivables in increasing profitability at PT. Pro Car INTL Finance Palopo Branch has not been effective, this is due to the large turnover of capital from consumers. The profitability ratio measured with ROE, ROI, NPM is quite good in accordance with the standard experts for ROE, ROI, NPM according to Lestari and Sugiarto 2007 which is > 2% based on the hypothesis proposed which states that the cash turnover of receivables at PT. Pro Car INTL Finance Palopo Branch has not been able to increase the company's profitability so that the proposed hypothesis is accepted because of cash turnover and efficient receivables. The Profitability Ratio shows that in PT. Pro Car INTL Finance Palopo Branch in 2007 - 2016 in generating annual profits increased from sales results in 2007 - 2016, so that the hypothesis proposed in this thesis was accepted which stated that additional sales can increase profitability in PT. Pro Car INTL Finance Palopo Branch in 2007 – 2016.